Menkes' disease: case report Doença de Menkes: relato de caso - Fabio Agertt; Ana C.S. Crippa; Paulo J. Lorenzoni; Rosana H. Scola; Isac Bruck; Luciano de Paola; Carlos E. Silvado; Lineu C. Werneck (Arquivos de Neuro-Psiquiatria)
Menkes’ disease is a rare neurodegenerative disorder due to an intracellular defect of a copper transport protein. We describe a 7 months male patient who presented with seizures, hypoactivity and absence of visual contact. The investigation disclosed pilli torti and thrycorrexis nodosa in the hair, low serum levels of both copper and ceruloplasmin, brain magnetic resonance study showed atrophy and white matter hypointensities on T1-weighted images, electroencephalogram reveals moderate background activity disorganization and epileptiform activity, and muscle biopsy with type 2 fiber atrophy. The clinical, laboratorial, genetic, muscle biopsy and neurophysiological findings in Menkes’ disease are discussed. A doença de Menkes é uma rara desordem neurodegenerativa causada por defeito intracelular na proteína transportadora do cobre. Descrevemos um paciente de 7 meses, masculino, com crises convulsivas, hipoatividade e ausência de contato visual. A investigação demonstrou pilli torti e thrycorrexis nodosa; níveis séricos baixos de ceruloplasmina e cobre; RNM de crânio com atrofia e redução de sinal da substância branca (imagens em T1); eletroencefalograma com moderada desorganização da atividade de base e atividade irritativa; e biópsia muscular com atrofia de fibras do tipo 2. As características clínicas, laboratoriais, genéticas, biópsia muscular e estudo neurofisiológico na doença de Menkes são discutidas.